MicroRNA-3145 as a potential therapeutic target for hepatitis B virus: inhibition of viral replication via downregulation of HBS and HBX - Muchtar, Amrizal; Onomura, Daichi; Ding, Dan; Nishitsuji, Hironori; Shimotohno, Kunitada; Okada, Shunpei; Ueda, Keiji; Watashi, Koichi; Wakita, Takaji; Iida, Kei; Yoshiyama, Hironori; Iizasa, Hisashi (Frontiers in Microbiology, 2025)
Current treatments for hepatitis B virus (HBV), such as interferons and nucleic acid analogs, have limitations due to side effects like depression and the development of drug-resistant mutants, highlighting the need for new therapeutic approaches. In this study, we identified microRNA-3145 (miR-3145) as a host-derived miRNA with antiviral activity that is upregulated in primary hepatocytes during HBV infection. The expression of its precursor, pri-miR-3145, increased in response to the the virus infection, and miR-3145 downregulated the hepatitis B virus S (HBS) antigen and hepatitis B virus X (HBX), thereby inhibiting viral replication. The binding site for miR-3145 was located in the HBV polymerase (pol) region, as experimentally confirmed. Moreover, overexpression of HBS and HBX induced pri-miR-3145 expression through endoplasmic reticulum stress. The expression of pri-miR-3145 showed a strong correlation with the Nance–Horan syndrome-like 1 (NHSL1) gene, as it is encoded within an intron of NHSL1, and higher NHSL1 expression in hepatocellular carcinoma patients with HBV infection was associated with better prognosis. These findings suggest that miR-3145-3p, along with small molecules targeting its binding sites, holds promise as a potential therapeutic candidate for HBV treatment.